Flexible Binder‐Free CuS/Polydopamine‐Coated Carbon Cloth for High Voltage Supercapacitors. Issue 9 (30th July 2018) - Yang, MinHo; Choi, Jaewon; Kim, Sung‐Kon; Braun, Paul V.
Abstract: Interfacial engineering is important to achieve high electrochemical performance in energy storage devices. It becomes particularly important for flexible devices, where stresses at the interface between the active material and current collector can be significant upon flexing. Here, we describe simple yet powerful method to tune surface properties, such as wettability and adhesion of carbon cloth (CC) as current collectors to active materials via using dopamine chemistry. We show how a polydopamine‐coated CC ( p ‐CC) exhibits strong adhesion with CuS nanosheets, enabling negligible capacitance fading after over 100 folding cycles. The CuS/ p ‐CC system exhibits attractive electrochemical properties, including a high specific capacitance (337 F g −1 at 0.5 A g −1 ), good rate capability (81.9 % capacitance retention at a rate of 10 A g −1 ), and excellent capacitance retention (about 96.1 % after 1000 cycles). An asymmetric supercapacitor fabricated by assembly of RGO/ p ‐CC and CuS/ p ‐CC provides a stable cell voltage up to 1.5 V and energy and power densities of up to 48.3 Wh kg −1 and 6919 W kg −1 on a full electrode basis. Abstract : The simple coating of polydopamine on carbon cloth enables fabrication of a binder free flexible supercapacitor electrode with excellent mechanical and cycling stability. An aqueous asymmetric supercapacitor based on this CuS/ p ‐CC positive and a RGO/ p ‐CC negative electrode delivers high specific energy and power, good rate capability, and excellent cycling stability.